Growth, physiological, and biochemical responses of Camptotheca acuminata seedlings to different light environments - Ma, Xiaohua; Song, Lili; Yu, Weiwu; Hu, Yuanyuan; Liu, Yang; Wu, Jiasheng; Ying, Yeqing (Frontiers in Plant Science, 2015)
Light intensity critically affects plant growth. Camptotheca acuminata is a light-demanding species, but its optimum light intensity is not known. To investigate the response of C. acuminata seedlings to different light intensities, specifically 100% irradiance (PAR, 1500±30 μmol m-2 s-1), 75% irradiance, 50% irradiance, and 25% irradiance, a pot experiment was conducted to analyze growth parameters, photosynthetic pigments, gas exchange, chlorophyll fluorescence, stomatal structure and density, chloroplast ultrastructure, ROS concentrations, and antioxidant activities. Plants grown under 75% irradiance had significantly higher total biomass, seedling height, ground diameter, photosynthetic capacity, photochemical efficiency and photochemical quenching than those grown under 100%, 25%, and 50% irradiance. Malondialdehyde (MDA) content, relative electrolyte conductivity (REC), superoxide anion (O2.-) production, and peroxide (H2O2) content were lower under 75% irradiance. The less pronounced plant growth under 100% and 25% irradiance was associated with a decline in photosynthetic capacity and photochemical efficiency, with increases in the activity of specific antioxidants (i.e., superoxidase dismutase, peroxidase, and catalase), and with increases in MDA content and REC. Lower levels of irradiance were associated with significantly higher concentrations of chlorophyll (Chl) a and b and lower Chla/b ratios. Stomatal development was most pronounced under 75% irradiance. Modification of chloroplast development was found to be an important mechanism of responding to different light intensities in C. acuminata. The results indicated that 75% irradiance is optimal for the growth of C. acuminata seedlings. The improvement in C. acuminata growth under 75% irradiance was attributable to increased photosynthesis, less accumulation of ROS, and the maintenance of the stomatal and chloroplast structure.